The risk of non‐melanoma skin cancer in New Zealand in inflammatory bowel disease patients treated with thiopurines. Issue 5 (14th February 2018) - Bahi, Morwan; Walmsley, Russell S; Gray, Andrew R; Young, David; Hobbs, Catherine E; Aluzaite, Kristina; Schultz, Michael
Abstract: Background and Aim: New Zealand (NZ) has one of the highest rates of non‐melanoma skin cancers (NMSCs) in the world. Thiopurine use in inflammatory bowel disease (IBD) patients has been shown to increase NMSC risk. This study aimed to investigate the possible increase of NMSC risk in thiopurine‐treated IBD patients in NZ despite the high background rate. Methods: Inflammatory bowel disease patients treated with thiopurines and healthy controls were recruited across two different latitude centers in NZ. Consented participants completed a questionnaire to identify additional risk factors and were examined for suspicious skin lesions. These were photographed, and the pictures were evaluated by a dermatologist. Data were compared between centers and between groups with NMSC incidence and thiopurine—associated relative risks estimated. Results: One hundred seventy‐one thiopurine‐exposed IBD patients and 201 controls were recruited. Twenty seven of 390 photographs (26 participants) showed suspicious lesions (17 exposed, 9 controls) as determined by the dermatologist. Estimated NMSC incidence was 24.7–34.3/1000 patient‐years (thiopurine‐exposed, depending on classification of unconfirmed suspicious lesions) and 7–14/1000 patient‐years (control). The relative risk of NMSC among thiopurine exposed was 2.38–2.97 ( P ≤ 0.014), which remained significant after individually adjusting for potential confounders. We estimated the NMSC risk to increase 5.4–6.6% per 6 months of thiopurine use ( P < 0.001). Low compliance in avoiding NMSC risk factors in the exposed group was observed. Conclusions: We found a twofold to threefold increase in NMSC incidence in IBD patients treated with thiopurines in NZ, despite the high background incidence rate.